Long leg cast versus hinged knee brace immobilization after surgical treatment of tibial tubercle fractures - Chizitam Ibezim, MD; Stephanie Price, MD; Christopher Souder, MD; Brian Kaufman, MD; Matthew Ellington, MD (Elsevier, 2024)
ABSTRACT: Background: Postoperative immobilization of tibial tubercle fractures (TTF) has historically been in the form of a long leg cast (LLC). The purpose of this study was to determine the functional outcome differences between LLC and hinged knee brace (HKB) in the postoperative management of TTF. Methods: We retrospectively reviewed TTF that underwent open reduction and internal fixation from May 2010 to February 2022 at a single Level 1 pediatric trauma center. Data parameters retrieved from the electronic medical record included: age, gender, body mass index, mechanism of injury, immobilization length of time, Immobilization type (HKB or LLC), time to full weight-bearing, time to return to play/sport, and time to full range of motion (ROM). Imaging was also reviewed to document Ogden classification, postoperative residual displacement, and time to radiographic fracture union. Differences in complications and management between the cohorts were evaluated. Results: A total of 64 patients (N = 65 TTF) were included for final analysis. Fifty fractures (76.9%) received a HKB while 15 (23.1%) were treated in an LLC. The mean age was 13.9 (±1.0) years, the gender composition was 92% male, and the mean body mass index was 25.6 (±5.7). There was no difference in the demographic data between cohorts. The median follow-up was 7 months (Interquartile Range 5-11 months). The main mechanism of injury was basketball (38.5%) and more than half of the TTF were Ogden type III (55.4%). The complication rate of the HKB cohort was 14% compared to 40% for the LLC cohort (P = .03). The HKB cohort returned to full ROM nearly 1 full month ahead of LLC patients (93 days vs 122 days, P = .02). There was no difference between the 2 groups with regard to time to full weight-bearing or return to play. There was also no difference in postoperative displacement or time to fracture union. Reduction with residual displacement greater than 4 millimeters was associated with delayed healing (104 days vs 60 days, P < .001). Conclusions: Patients who sustain TTF can be effectively rehabilitated postoperatively in an HKB. HKB displayed expedited ROM recovery and was associated with a lower complication rate. Key Concepts: (1) Tibial tubercle fractures patients can be effectively rehabilitated postoperatively in an Hinged knee brace. (2) Those treated with Hinged knee brace vs Long leg cast displayed expedited ROM recovery. (3) Those treated with Hinged knee brace vs Long leg cast were associated with a lower complication rate. Level of Evidence: III